The Bible in Ethiopia : the Book of Acts. - Niccum, Curt, 1962- (Ethiopic manuscripts, texts and studies, 2014)
The Ethiopic version provides a window into the state of the Greek Bible as it circulated in East Africa at the end of the fourth century. It is, therefore, an extremely important witness to the Bible's early transmission history, yet its testimony has typically been ignored or misunderstood by text critics. This study examines the history of the book of Acts in Ethiopia and reconstructs its earliest attainable text, which then is assessed using the latest text-critical methods. It therefore provides a solid base for interpreting the data of this key witness and lays the groundwork for future text-critical work in Ethiopic and other early versions.